2017
DOI: 10.1016/j.athoracsur.2017.05.016
|View full text |Cite
|
Sign up to set email alerts
|

Surgical Ablation of Atrial Fibrillation in the United States: Trends and Propensity Matched Outcomes

Abstract: Contemporary utilization of SA is increasing across all operative categories. Performance of SA is accompanied by a 30-day reduction in mortality and stroke. These findings further refine our understanding of the role of SA in the treatment of AF.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
193
2
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 174 publications
(202 citation statements)
references
References 26 publications
5
193
2
2
Order By: Relevance
“…No randomized controlled trial has shown clear clinical improvements and only some personal series have suggested benefits in stroke or survival (5)(6)(7)(8). But very recent data analysis from the STS database matching 28,739 patient-pairs with and without AF described that surgical ablation was associated with a reduction in mortality and stroke, while an increase in renal failure and the need for pacemaker implantation (9). Most probably, surgical ablation for AF really reduces long-term mortality and risk for stroke, but to demonstrate this benefit a big population with a long follow-up is needed.…”
Section: Why To Treat Af In Mitral Insufficiencymentioning
confidence: 99%
“…No randomized controlled trial has shown clear clinical improvements and only some personal series have suggested benefits in stroke or survival (5)(6)(7)(8). But very recent data analysis from the STS database matching 28,739 patient-pairs with and without AF described that surgical ablation was associated with a reduction in mortality and stroke, while an increase in renal failure and the need for pacemaker implantation (9). Most probably, surgical ablation for AF really reduces long-term mortality and risk for stroke, but to demonstrate this benefit a big population with a long follow-up is needed.…”
Section: Why To Treat Af In Mitral Insufficiencymentioning
confidence: 99%
“…In 2017 STS guidelines, concomitant atrial fibrillation (AF) ablation gained IA recommendation in patients with AF undergoing mitral surgery and IB recommendation when undergoing coronary or aortic valve surgery . A recent report from the STS database, shows that between 2013 and 2017 concomitant AF ablation was performed in nearly 50% of patients in AF undergoing mitral surgery in US …”
Section: Introductionmentioning
confidence: 99%
“…A common dilemma while performing surgical AF ablation as a concomitant procedure, particularly during mitral surgery is deciding between a full set of lesions on both atria (BA) or to limit the ablation only to the left atrium (LA), which is already opened for the correction of mitral valve disease. According to the STS database, these two approaches are adopted with similar frequencies (45% vs 50%) . Therefore, the primary end point of the present study is to meta‐analyze the studies available in the literature to evaluate the efficacy and the safety of BA vs LA approach.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…По результатам оценки в группе пациентов, перенесших вмеша-тельство на открытом сердце [1][2][3][4], конкоми-тантная хирургическая аблация ФП эффективно восстанавливает синусовый ритм и улучшает ка-чество жизни. До настоящего времени не сфор-мировалось единого мнения относительно опти-мальной схемы нанесения разрезов (аблацион-ных линий) для лечения ФП при выполнении вмешательств на сердце.…”
Section: Introductionunclassified